Metastatic breast cancer incidence, site and survival in Australia, 2001–2016: a population-based health record linkage study protocol. Issue 2 (1st February 2019) - Lord, Sarah J; Kiely, Belinda E; Pearson, Sallie-Anne; Daniels, Benjamin; O'Connell, Dianne L; Beith, Jane; Bulsara, Max K; Houssami, Nehmat
Abstract : Introduction: Advances in systemic therapy for early and metastatic breast cancer (BC) over the last two decades have improved patients' survival, but their impact on metastatic disease outcomes at a population level is not well described. The aim of this study is to investigate changes in the incidence, site and survival of metastatic disease for women with a first diagnosis of BC in 2001–2002 vs 2006–2007. Methods and analysis: Population-based retrospective cohort study of women with first primary invasive BC registered in the New South Wales (NSW) Cancer Registry in 2001–2002 and 2006–2007. We will use linked records from NSW hospitals, dispensed medicines, outpatient services and death registrations to determine: women's demographic and tumour characteristics; treatments received; time to first distant metastasis; site of first metastasis and survival. We will use the Kaplan-Meier method to estimate cumulative incidence of distant metastasis, distant recurrence-free interval and postmetastasis survival by extent of disease at initial diagnosis, site of metastasis and treatment-defined tumour receptor type (hormone receptor-positive, human epidermal growth factor receptor-2-positive, triple negative). We will use Cox proportional hazards regression to estimate the relative effects of prognostic factors, and we will compare systemic therapy patterns by area-of-residence and area-level socioeconomic status to examine equity of access to healthcare. Ethics and dissemination: Research ethics committee approval was granted by the Australian Institute of Health and Welfare (#EO2017/2/255), NSW Population and Health Services (#HREC/17/CIPHS/19) and University of Notre Dame Australia (#0 17 144S). We will disseminate research findings to oncology, BC consumer and epidemiology audiences through national and international conference presentations, lay summaries to BC consumer groups and publications in international peer-reviewed oncology and cancer epidemiology journals.